Microstructural control of LPBF Inconel 718 through post processing of intentionally placed AM discontinuity distributions - Livera, E. R.; Christofidou, K. A.; Miller, J. R.; Chechik, Lev; Ryan, D.; Shrive, J.; Todd, I. (Materialia, 2024)
A major untapped potential of laser powder bed fusion (LPBF) is the ability to additively manufacture (AM) parts with site-specific properties. However, robust methods of improving performance and manufacturing efficiency via spatial variations in microstructure are underexplored. This work investigates a method of creating several distinctive multi-modal microstructures in the nickel superalloy, Inconel 718, by performing a Hot Isostatic Pressing (HIP) procedure on characteristic LPBF discontinuities such as keyhole and lack of fusion (LOF) porosity, as well as large powder filled voids. Observed using electron backscattered diffraction, this approach leads to the formation of site-specific variations in microstructure and extreme bi-modal microstructures. Processing AM parts via this method facilitates the production of fully dense, equiaxed, and strain free material culminating in a substantial time saving per layer. Further optimisation is required in order to achieve an optimum volume fraction and distribution of γ″ precipitates in each heat treated microstructure.
Created from Fastlane, Scopus look-up
Keywords: Additive manufacturing; Bi-modal microstructures; Functional grading; Increased productivity; Laser powder bed fusion; Microstructural control; Nickel superalloys